Victims of Crime - Khac Hai, Nguyen (VNU Journal of Science: Legal Studies; Vol 34 No 2, 2018)
The research clarifies basic issues related to victim of crime as a social and legal phenomenon. This study defines victim of crime, analyses victimization and its causes based on the theories as lifestyle model, routine activity approach and opportunity. Besides, the article studies the international standards and the rights of victims like access to justice and fair treatment, restitution, compensation, and assistance. The role of victim of crime in the criminal justice system and government’s responsibility are also the core issues discussed in the research. Keywords Victim of crime, victimology, victimization, rights of victim of crime. References [1] Victimmology (Sixth Edition) (2012), Villiam G.Doerner and Steven P.Lab Anderson, Publishing (Elsevier) USA. [2] Andrew Karmen (2013). Crime Victims – An Introduction to Victimology. Wadsworth, Cengage Learning, USA. [3] Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power (UN General Assembly resolution 40/34 of 29 November 1985, Annex A). [4] Gerd Ferdinand Kirchhoff. What is Victimology?. Monograph Series No.1. Seibundo Publishing. Japan. 2005. [5] Stephen Schafer: The Victim and His Criminal. New York: Random House. 1968. [6] ЧастнаяКриминология. Под. ред. ШестаковД.А. СанктП. 2007. [7] [Frank Schmalleger and Rebecca Volk (2005). Canadian Criminology Today: Theories and Applications (Second Edition). Pearson Pretice Hall. Toronto. [8] Handbook on Criminal Justice Responses to Terrorism. United Nations. New York. 2009. [9] Universal Declaration of Human Rights, article 8; Declaration on the Protection of All Persons from Being Subjected to Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment (UN General Assembly resolution 3452 (XXX), annex), article 11. [10] Declaration of Basic Principles of Justice for Victims of Crime and Abuse of Power (UN General Assembly resolution 40/34 of 29 November 1985). [11] Raising the Global Standards for Victims: The proposed Convention on Justice for Victims of Crime and Abuse of Power. Seibundo Publishing. John P.J. Dusich and Kieran G. Mundy edited. Tokyo, Japan. 2009. [12] Basic Principles and Guidelines on the Right to a Remedy and Reparation for Victims of Gross Violations of International Human Rights Law and Serious Violations of International Humanitarian Law (UN General Assembly resolution 60/147 of 16 December 2005). [13] United Nations Convention against Transnational Organized Crime, articles 24 and 25; United Nations Convention against Corruption, article 32. [14] Establishing Victimology. Festschrift for Prof.Dr.Gerd Ferdinand Kirchhoff. 30 th Anniversary of Dubrovnik Victimology Course. Peter Schafer, Elmar Weitekamp. [15] Villiam G.Doerner and Steven P.Lab (2012), Victimmology (Sixth Edition), Anderson Publishing (Elsevier) USA. [16] Gerd Ferdinand Kirchhoff. What is Victimology?. Monograph Series No.1. Seibundo Publishing Co.,Ltd. Japan. 2005. [17] Victimology and Human Security: New Horizons. Selection of papers presented at the 13 th International Syposium on Victimology, 2009, Mito, Japan. Morosawa, Hidemichi Dusich, John J.P, Kirchhoff, Gerd Ferdinand, Wolf Legal Publishers, The Netherlands. [18] Marquart, J. W. (2005). Editorial introduction: Bringing victims in, but how far? Criminology & Public Policy, 4. [19] The Study of Victimology -Basic considerations for the study of theoretical victimology. Gerd Ferdinand Kirchhoff and Hidemichi Morosawa. (Victimization in a multi-disciplinary key: Recent advances in victimology). Wolf Legal Publishers. The Netherlands. 2009.